A quantitative analysis of Augmented Reality visual merchandising on online purchase intention: A consumer neuroscience approach - Abbott, Lara Elizabeth (School of Management Studies, 2023)
The rapid evolution of e-commerce has led retailers to fixate on how to differentiate themselves and provide an enhanced and engaging experience for their customers. In this dynamic industry, emerging technologies and innovation have become crucial for maintaining a competitive advantage. The purpose of this study is to explore how newer methods of visual merchandising can influence consumer purchase intentions, paying particular attention to Augmented Reality (AR) and how its inclusion in the online shopping industry could mark a pivotal change. The study addresses present difficulties in online retail such as the lack of touch and feel aspect, customer uncertainty and cart abandonment. It is proposed herein that Augmented Reality as a visual merchandising technique will mitigate these difficulties and allow South African online retail to grow in accordance with global standards. Given the recent developments in online retail in South Africa due to the COVID-19 pandemic, it is an opportune moment to investigate consumers and invest in meeting their ever-changing needs, enhancing their experiences, and formulating insight-driven digital marketing strategies. This paper serves to break new ground in nascent AR literature within the field of market research, and particularly in the South African and Neuroscience context. By examining the real-time Emotion and Attention of respondents using Neuroscience technology, this study provides a practical approach for marketing executives to optimize their customers' online experience and thus drive conversion rates. The objectivity of neuroscience methods presented more reliable, evidence-driven insights by accessing unconscious consumer responses that complement traditional measures. The Technology Acceptance Model (TAM), a robust and frequently used model for new technology adoption and the Model of Emotion Regulation were also used, providing the explicit measures for the study. Perceived Ease of Use, Perceived Usefulness and Purchase Intention were all rated favorably, indicating a positive likelihood of AR adoption by the South African market. The positive feedback regarding Purchase Intention is also a significant finding given it has proven previously to be an indicator of actual buying behaviour. Higher levels of arousal in the AR group present a promising indication of the consumers' cognition of the product and ultimately its impact on the consumer decision making process. Therefore, this study suggests the incorporation of AR into marketing strategies to remain successful in a dynamic retail environment.